TIK DI PERDESAAN DENGAN PENDEKATAN OUTPUT BASED AID - Andika, Prana (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
This research discusses the implementation of GPOBA assistance relief which is an output based aid. The regional assistance of GPOBA relief covered Lampung Province, West Java Province and Banten Province. The aid of telecommunication assistance was a catalyst from the World Bank and Ministry of Communication and Informatics in order to reduce gap of information between urban and rural communities. Aid relief applied in several stage accordance with the results of output that have been done before. This study use a qualitative approach and then analyzed descriptively. Secondary data collection obtained from Report Preparation Section on General Secretary of Directorate Application Informatics and conduct interview with managerial staff of GPOBA program and data literature. Research results found that in general GPOBA program has done well despite some problem that still occured in several operated internet cafÃ©. There are several constraint that associated with technical difficulties of ICT equipment, location placement and managerial of village internet cafÃ©.